Ergonomic Risk Assessment to Improve Worker Safety in Assembly Line Operations - Gunawan, Olivia Adeline; Colim, Ana; Duffy, Vincent G. (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Ergonomic risks in assembly line operations remain a major contributor to work-related musculoskeletal disorders and reduced productivity. Assembly work is characterized by repetitive motions, awkward postures, forceful exertions, and time pressure, which together increase physical strain on workers. This study aims to develop and apply an integrated ergonomic risk assessment framework to improve worker safety in assembly line operations. The research adopts a descriptive–analytical design by combining observational ergonomic assessment methods, digital ergonomics tools, and multi-criteria decision-making techniques. Data were collected from representative assembly workstations through direct observation, posture analysis, and task cycle evaluation. The results indicate that several workstations exhibit high ergonomic risk levels, particularly related to upper limb posture, repetitive actions, and static loading. By applying integrated assessment approaches such as REBA, RULA, OCRA-based indicators, and decision-support techniques, targeted improvement strategies were identified, including workstation redesign, task redistribution, and job rotation. The discussion demonstrates that the proposed approach aligns with and extends previous ergonomic studies by providing a systematic and scalable framework suitable for mixed-model assembly lines. The study concludes that integrated ergonomic risk assessment significantly enhances worker safety while supporting operational efficiency, offering practical implications for manufacturing practitioners and directions for future research.